2022
DOI: 10.1021/acs.chemrev.2c00439
|View full text |Cite
|
Sign up to set email alerts
|

Methane Oxidation to Methanol

Abstract: The direct transformation of methane to methanol remains a significant challenge for operation at a larger scale. Central to this challenge is the low reactivity of methane at conditions that can facilitate product recovery. This review discusses the issue through examination of several promising routes to methanol and an evaluation of performance targets that are required to develop the process at scale. We explore the methods currently used, the emergence of active heterogeneous catalysts and their design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
108
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 374 publications
0
108
0
1
Order By: Relevance
“…It is found that there are no products (CH 3 OH, HCHO, CO, and CO 2 ) detected without the addition of photocatalysts. Isotope labeling is performed by using 13 CH 4 to replace 12 CH 4 as the reactant. As shown in Figure S13, there are signals assigned to 13 CH 4 (m/z = 17), 13 CH 3 OH (m/z = 33), and H 13 CHO (m/ z = 31) detected over the BN sample.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that there are no products (CH 3 OH, HCHO, CO, and CO 2 ) detected without the addition of photocatalysts. Isotope labeling is performed by using 13 CH 4 to replace 12 CH 4 as the reactant. As shown in Figure S13, there are signals assigned to 13 CH 4 (m/z = 17), 13 CH 3 OH (m/z = 33), and H 13 CHO (m/ z = 31) detected over the BN sample.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Under such circumstances, it is required with urgency to develop alternative routes to achieve highly selective oxidation of CH 4 to value-added products under moderate conditions. [12] Since the occurrence of the dehydrogenation process is caused by the cleavage of CÀ H bonds (cf. Figure 1a), induction of cleavage of other hydrogen bonds to replace CÀ H bonds might prevent continuous dehydrogenation in target products.…”
Section: Introductionmentioning
confidence: 99%
“…Methane (CH 4 ) as the main greenhouse gas has also been recognized as one of the most important chemical raw materials for higher value liquid fuels and chemicals, such as formic acid, methanol, olefins, aromatics, acetic acid, dimethyl ether, etc. Because of its widespread distribution and renewable characteristics, about 90% of methane is burned to produce electricity and heat, and it has been becoming indispensable to the sustainable development of the human society. The release of CH 4 with an ineffective treatment into the atmosphere may cause the greenhouse effect 80 times more powerful than carbon dioxide (CO 2 ), and accelerates the permafrost thawing. , However, the utilization of CH 4 from natural gas, shale gas, biogas, etc., is seriously limited by its natural geographical barriers and high transportation energy costs .…”
Section: Introductionmentioning
confidence: 99%
“…Methanol (CH 3 OH) is a promising chemical with high capability of hydrogen storage and broad application in the fuel cell, which can be directly obtained by the selective oxidation of CH 4 . Whereas, due to the strong C–H bond (435 kJ mol –1 ) of CH 4 , there remain significant challenges in its activation and avoiding overoxidation for the direct transformation of CH 4 to CH 3 OH . Industrial methane conversion usually consists of a multistep process such as the production of syngas under harsh operating conditions, resulting in large energy consumption, high cost, and low efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation